A case report of primary sternal osteomyelitis caused by polymicrobial bacteria, including Actinomyces israelii. (2020) - Hamanaka, Ryosuke; Hashimoto, Takehiro; Mizukami, Eri; Okutsu, Yuki; Masutomo, Kazuhiro; Komiya, Kosaku; Nureki, Shin-ichi; Shimoda, Katsuhiro; Hiramatsu, Kazufumi
Highlights: Actinomyces species colonize the human oropharynx, gastrointestinal tract, and urogenital tract. Primary sternal osteomyelitis is very rare, especially caused by Actinomyces israelii. Actinomycosis requires long-term antibiotic treatment. A. israelii should be included in the differential diagnosis as a causative pathogen of osteomyelitis. Abstract: We herein report a case of primary sternal osteomyelitis caused by polymicrobial bacteria, including Actinomyces israelii . A 72-year-old man presented with a fever and precordial pain. Chest computed tomography (CT) revealed peristernal fluid associated with an osteolytic lesion and a peripheral nodule in the right upper lobe. We suspected sternal osteomyelitis, and an incision and drainage were performed. Culture of the drainage fluid and bone tissue yielded A. israelii, Fusobacterium necrophorum, and Streptococcus constellatus . Treatment with benzylpenicillin potassium (PCG) was administered. A subsequent chest CT scan showed that the peripheral nodule decreased in size after antimicrobial therapy. We therefore presumed the peripheral nodule as septic pulmonary embolism(SPE). Antimicrobial agents were administered for a total of 6 months. To our knowledge, this is the first case report of primary sternal osteomyelitis associated with presumed SPE caused by polymicrobial bacteria, including A. israelii . It is important to identify the causative pathogen in osteomyelitis, which requires long-term antibiotic treatment.